Pelatihan Pemanfaatan Gemini AI dalam Pembuatan Aplikasi Mobile untuk Guru TIK Lampung Selatan - Muhaqiqin; Mohamad Zainudin; Ridho Sholehurrohman; Igit Sabda Ilman; Wartariyus; Riska Amalia Praptiwi; Istiana Ruswita (Journal Social Science And Technology For Community Service, 2025)
This community service activity aimed to enhance the digital literacy and skills of ICT teachers in South Lampung in developing educational mobile applications using Gemini AI, given that most teachers had not mastered application programming or the use of AI in teaching. The offline training, held on July 27, 2025, at SMA Negeri 1 Kalianda, involved 25 ICT teachers and integrated practical-based training, the diffusion of Gemini AI science and technology, and intensive technical assistance. The material covered basic AI concepts, Gemini AI implementation with Android Studio Cloud, and practical prototype development for applications like practice questions and ICT dictionaries. As a result, 92% of participants found the training very helpful, and teachers successfully created AI-based application prototypes. This activity successfully improved teachers' literacy and skills, demonstrating their significant potential in developing learning technology. Further training with gradual difficulty levels, increased practice time, and program expansion are recommended to strengthen the digital learning ecosystem.